The impact of decision-making profiles on the consistency of rankings obtained by means of selected multiple criteria decision-aiding methods - Roszkowska, Ewa; Wachowicz, Tomasz (Wpływ profilu decyzyjnego na zgodność rankingów otrzymanych za pomocą wybranych metod wielokryterialnych – analiza badania eksperymentalnego, 2019)
The paper discusses the impact of the decision-making profiles on the consistency of rankings obtained by three multiple criteria methods, i.e. DR, AHP and TOPSIS. The online decision making experiment was organized, based on an electronic questionnaire which is a hybrid of the internet survey system and the decision support system. The participants of the experiment were 418 students of Polish universities. To describe the decision-making profile, the REI test was used which allows to distinguish two decision-making styles: rational and intuitive. The Kendall rank correlation coefficient was used to test the consistency of the rankings obtained by the considered methods. Using different grouping methods, the relationship between the decision profile and the ability to express one’s preferences by means of these methods, that differ in cognitive requirements, was examined. The results of the research may be helpful for supporting the decision-maker in decision processes by choosing the method that fits their profile best
Econometrics = Ekonometria, 2019, Vol. 23, No. 2, s. 9-14
Keywords: decision support; decision-making profile; multiple criteria; decision aiding; preference analysis; data analysis; wspomaganie podejmowania decyzji; profil decyzyjny; metody wielokryterialne; analiza preferencji; analiza danych